2018
DOI: 10.3389/fnagi.2018.00147
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Proprioceptive Processing Is Altered by Aging

Abstract: Proprioceptive perception is impaired with aging, but little is known about aging-related deterioration of proprioception at the cortical level. Corticokinematic coherence (CKC) between limb kinematic and magnetoencephalographic (MEG) signals reflects cortical processing of proprioceptive afference. We, thus, compared CKC strength to ankle movements between younger and older subjects, and examined whether CKC predicts postural stability. Fifteen younger (range 18–31 years) and eight older (66–73 years) sedenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 72 publications
12
58
0
Order By: Relevance
“…2017; Watanabe et al., 2018a). Perhaps OLDER needed to up‐regulate the vestibular/somatosensory information to counteract deficiencies in, for example, proprioception (Piitulainen, Seipäjärvi, Avela, Parviainen, & Walker, 2018) in order to control posture in the eyes‐open task to the same level as YOUNG. Otherwise, the greater low frequency (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…2017; Watanabe et al., 2018a). Perhaps OLDER needed to up‐regulate the vestibular/somatosensory information to counteract deficiencies in, for example, proprioception (Piitulainen, Seipäjärvi, Avela, Parviainen, & Walker, 2018) in order to control posture in the eyes‐open task to the same level as YOUNG. Otherwise, the greater low frequency (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced brain activation in this region in response to proprioceptive stimulation could reflect a loss of proprioceptive integration in older adults. In this vein, Piitulainen et al (2018) reported that cortical processing of the proprioceptive signal is altered by aging. Furthermore, Ozdemir et al (2018) indicated that impairments in perceptual processing of sensory signals contribute to prolong muscle response delays during perturbed upright standing in older adults.…”
Section: Signal Integrationmentioning
confidence: 99%
“…Proprioception is impaired with aging (Kaplan et al, 1985) and this is considered to be one of the main contributors to loss of balance in older adults (Lord and Ward, 1994). Proprioception is not solely a peripheral phenomenon, and recently we have observed impaired proprioceptive processing within the primary sensorimotor cortex (SM1; Piitulainen et al, 2018). These age-related maladaptations suggest altered neuronal motor control, but the exact causes of the modified neuronal control in various conditions (e.g., during perturbed balance control) remain elusive.…”
Section: Introductionmentioning
confidence: 99%